2020
DOI: 10.1177/1359104520945390
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition in children with externalising behaviours: A systematic review

Abstract: Difficulties in facial emotion recognition (FER) are associated with a range of mental health and antisocial presentations in adolescents and adults. Externalising behaviours in children are often one of the earliest signs of risk for the development of such difficulties. This article systematically reviews the evidence (from both group and correlational studies) for whether there is a relationship between FER and externalising behaviours in pre-adolescent children (aged 12 and under), both across and within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 79 publications
(138 reference statements)
2
13
0
Order By: Relevance
“…The results of studies examining the effect of MPH on emotion recognition in children with ADHD are somewhat contradictory. Both Gumustas et al [ 101 ] and Hall et al [ 102 ] did not find significant differences between a TD control group and children with ADHD that were tested while unmedicated, in contradiction of previous findings that show impairments [ 25 , 113 ]. Thus, it is possible that their study design was not sensitive to the relevant deficits that are characteristic in children with ADHD, and so their additional observation that MPH (either after a 12 week-long medication regime [ 101 ] or while conducting the test [ 102 ]) had no statistically significant effect on performance is inconclusive.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results of studies examining the effect of MPH on emotion recognition in children with ADHD are somewhat contradictory. Both Gumustas et al [ 101 ] and Hall et al [ 102 ] did not find significant differences between a TD control group and children with ADHD that were tested while unmedicated, in contradiction of previous findings that show impairments [ 25 , 113 ]. Thus, it is possible that their study design was not sensitive to the relevant deficits that are characteristic in children with ADHD, and so their additional observation that MPH (either after a 12 week-long medication regime [ 101 ] or while conducting the test [ 102 ]) had no statistically significant effect on performance is inconclusive.…”
Section: Discussionmentioning
confidence: 78%
“…Communication of emotions via nonverbal cues may be more complex, but is also a relatively universal skill (see, for example, [ 111 ]) that is closely linked to attention [ 112 ]. Studies to date suggest that children with ADHD experience some impairment in the recognition of emotional facial expressions [ 25 , 113 ], although broadly differing results vary as to the specific emotions that present challenges. Since MPH is known to increase sustained attention in children with ADHD (see, for example, [ 114 116 ]), it is reasonable to assume that children with ADHD would perform better on emotion recognition tasks while medicated with MPH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that patients with conduct problems show impairments in facial emotion recognition [36]; however, the etiology remains unclear. In this regard, Martin-Key and colleagues examined the function of eye fixation on emotionally informative face regions in CD subjects and found a minor effect for abnormalities in fixation behaviors; therefore, they attributed impaired recognition of facial expressions to problems in the comprehension of emotional signs [37].…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in emotion recognition are well documented in children and adolescents with a range of mental health, neurodevelopmental and behavioral issues, indicating that impaired emotion recognition is a transdiagnostic risk factor (Collin, Bindra, Raju, Gillberg and Minnis, 2013;Cooper, Hobson & Van Goozen, 2020). In individuals with ASB, reduced emotional awareness and a failure to recognize cues from the environment that signal threat, distress or submission can lead to a lack of empathy or guilt, which may continue and intensify the problematic behavior (Blair, 2005;.…”
Section: Children With Severe Asb Have Impairments In Recognizing Negative Emotions and In Empathy For Other's Distressmentioning
confidence: 99%